Gay, Bisexual, and Queer Men’s Attitudes and Understandings of Intimate Partner Violence and Sexual Assault - Salter, Michael (Journal of interpersonal violence, 2021)
Gay, bisexual, and queer (GBQ) men experience significant rates of intimate partner violence (IPV) and sexual assault (SA); however, there is limited research into their attitudes and understandings of IPV and SA. This article presents the findings of a 2018 survey of 895 GBQ men currently residing in Australia, focused on their views and experiences of healthy and unhealthy relationships. The survey included quantitative and open-ended qualitative questions. The findings presented in this article are primarily descriptive, with cross-tabulations and t tests to demonstrate significant differences between groups and correlational statistics to outline associations between variables. Qualitative data were coded under broad themes. The study found a considerable proportion of men (three in five) identified that they had experienced an unhealthy or abusive relationship in the past, with minimal disclosure to police or health services. Men with a history of partner abuse or violence were more likely to report binge drinking or drug use and more likely to know a friend who had abused his partner. 40% of the sample had witnessed an incident of relationship violence between GBQ men, and two-thirds intervened in the violence in some way. The findings of this study underscore the need to engage GBQ men in discussions about respectful relationships, address the role of alcohol and drugs in GBQ socialization and relationships, and provide bystander skills for men to intervene in situations of aggression or violence between men in relationships.